Minimally invasive surgery for severe hallux valgus in 106 feet. Issue 4 (June 2022) - Lewis, T.L.; Ray, R.; Gordon, D.J.
Abstract: Background: There is widespread variation in the optimal procedure for correction of severe hallux valgus deformity defined as hallux valgus angle (HVA) (≥40°) and/or 1–2 intermetatarsal angle (IMA) (≥20°). There is limited evidence investigating the clinical or radiological outcomes following treatment of severe hallux valgus deformity with third-generation minimally invasive chevron and Akin osteotomies (MICA). Methods: This was a prospective observational single surgeon series of consecutive patients who underwent primary third-generation MICA with screw fixation for severe hallux valgus. The primary outcome was a validated patient reported outcome measure (PROM), the Manchester-Oxford Foot Questionnaire (MOXFQ), assessed minimum 2 years following MICA. Secondary outcomes were radiographic deformity correction (assessed 6 weeks post-operatively), complication rates and other quality of life PROMs (EQ-5D and Visual Analogue Pain Scale). Results: Between September 2014 and November 2018, 106 consecutive feet (n = 78 patients; 73 female, 5 male) met the inclusion criteria. Prospectively collected pre-operative and 2 year PROM MOXFQ data was available for 86 feet (81.1%). At two years following surgery, the MOXFQ score significantly improved for the Pain, Walking and Standing and Social Interaction domains from 39.2 to 7.5, 38.2 to 5.9 and 48.6 to 5.5, respectively (p < 0.001). Pre- and 6 week post-operative radiographic data was available for all 106 feet. Mean IMA improved from 18.2° to 6.3° (p < 0.001) whilst mean HVA improved from 45.3° to 10.9° (p < 0.001). The complication rate was 18.8% and the screw removal rate was 5.6%. Conclusion: This study has demonstrated third-generation MICA for the treatment of severe hallux valgus deformity enables substantial deformity correction and is associated with significant improvements in clinical PROMs 2 years following surgery.